Structural analysis of dental fear in children with and without dental trauma experience - Bakarčić, Danko; Ivančić Jokić, Nataša; Majstorović, Martina; Škrinjarić, Ana; Zarevski, Predrag (2007)
The aim of the study was to evaluate dental fear in children with and without dental injuries in a randomly selected children in Croatia (59 girls and 88 boys). Children were divided into three groups depending on dental trauma experience. They were also divided into two age groups: 5-8 and 9-12 years. Only dental trauma to the permanent teeth was included in the study. The CFSS-DS, CDAS and CMFQ were used for evaluation of dental anxiety and the ISP Hollingshead Index of Social Position was calculated for evaluation of social status. The mean values of CDAS, CFSS-DS and CMFQ tests revealed that the anxiety level decreases with increasing experience of dental injury. The analysis of variance performed for CDAS showed a significant difference between children with and without dental trauma (p = 0, 010). Regarding the groups, the analysis of variance for CMFQ (p = 0, 021) and CFSS-DS (p = 0, 001) showed a significant difference, as well as regarding age (CMFQ ; p = 0, 001 and CFSS-DS ; p = 0, 016). Cronbach's alpha coefficients revealed the highest reliability for CFSS-DS (alpha = 0, 910). Pearson's correlation coefficients revealed significant correlations between the anxiety scores, age and ISP values for children without dental trauma, and between the anxiety scores and age for children with repeated dental trauma. The results of the ISP Hollingshead Index exhibited the highest frequency in children with dental injuries who belonged to the families with poor social background (ISP = 44-60). No significant difference was obtained between children with and without dental injuries depending on either gender or the ISP value.
Projekt MZOS
Projekt MZOS
ENG